2012
DOI: 10.1007/s00705-012-1410-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and serological detection of bat coronavirus from bats in the Philippines

Abstract: Bat coronavirus (BtCoV) is assumed to be a progenitor of severe acute respiratory syndrome (SARS)-related coronaviruses. To explore the distribution of BtCoVs in the Philippines, we collected 179 bats and detected viral RNA from intestinal or fecal samples by RT-PCR. The overall prevalence of BtCoVs among bats was 29.6 %. Phylogenetic analysis of the partial RNA-dependent RNA polymerase gene suggested that one of the detected BtCoVs was a novel alphacoronavirus, while the others belonged to the genus Betacoron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 20 publications
5
27
0
1
Order By: Relevance
“…In two species with relatively large sample sizes (Miniopterus australis and M. schreibersii in south-east Queensland), 25% of 154 individuals and 27% of 238 individuals, respectively, were positive for coronavirus RNA. Studies elsewhere have shown similar prevalence rates (Tsuda et al 2012;Suzuki et al 2014); others have reported much lower prevalence (Anthony et al 2013). Seroprevalence in our study was also high in some populations, including those that were negative for viral RNA.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In two species with relatively large sample sizes (Miniopterus australis and M. schreibersii in south-east Queensland), 25% of 154 individuals and 27% of 238 individuals, respectively, were positive for coronavirus RNA. Studies elsewhere have shown similar prevalence rates (Tsuda et al 2012;Suzuki et al 2014); others have reported much lower prevalence (Anthony et al 2013). Seroprevalence in our study was also high in some populations, including those that were negative for viral RNA.…”
Section: Discussionsupporting
confidence: 81%
“…In some cases, the limited sample size may have constrained detection of viral RNA in the sampled population. Although there have been fewer serological studies than molecular studies in bats, others have also found high coronavirus antibody prevalence in some bat species, albeit using a different serological assay (Tsuda et al 2012). Indeed, given that our ELISA was based on SARS-CoV antigens, it may be that broader coronavirus seroprevalence is underestimated.…”
Section: Discussionmentioning
confidence: 94%
“…A significant diversity of CoVs was found in pteropodids both in Cambodia and Lao PDR. Overall, CoV detection rates (6.5% in Lao PDR and 4.85% in Cambodia) were in the same range as those found in Thailand (7%) (Wacharapluesadee et al, 2015), but lower than those reported in Hong Kong (12%) or Philippines (29.6%) (Tsuda et al, 2012;Woo et al, 2006). Interestingly, for the first time, coronaviruses were detected in Megaerops niphanae and Myotis horsfieldii.…”
Section: Discussionsupporting
confidence: 55%
“…Bats have been identified as the natural host of the SARS-CoV, , and recently, the NeoCoV from the clade the Middle Eastern Respiratory Syndrome (MERS-CoV) was detected in a sub-Saharan bat (Neoromicia capensis) besides its camel host (Corman et al, 2014). A growing number of coronaviruses have been detected in bats since the SARS-CoV outbreak (Chu et al, 2006(Chu et al, , 2008Lau et al, 2007Lau et al, , 2010Lau et al, , 2012Watanabe et al, 2010;Gouilh et al, 2011;Tsuda et al, 2012;Wacharapluesadee et al, 2013Wacharapluesadee et al, , 2015Anindita et al, 2015;Xu et al, 2016, Kim et al, 2016 including a high diversity of coronaviruses, recently detected in five Thai provinces neighboring Cambodia (Wacharapluesadee et al, 2013(Wacharapluesadee et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…These ectoparasites are of veterinary importance as potential vectors that enable pathogens and potentially pathogenic microorganisms to bypass barriers such as fur and skin (Messenger et al, 2003;Dick and Patterson, 2006). In the Philippines, bats were recently shown to harbour parasitic protozoans (Murakoshi et al, 2016) and viruses (Watanabe et al, 2010;Taniguchi et al, 2011;Tsuda et al, 2012), although their zoonosis are still indefinite. Bat flies are also reported to harbour fungi belonging to Order Laloulbeniales (Blackwell, 1980;Marshall, 1982).…”
Section: Introductionmentioning
confidence: 99%